Effect of 15 days −6° head-down bed rest on microbial communities of supragingival plaque in young men - Zhu, Di; Qiao, Pengyan; Zhou, Qian; Sun, Hui; Xin, Bingmu; Wu, Bin; Tang, Chuhua (Frontiers in Microbiology, 2024)
The microgravity environment astronauts experience during spaceflight can lead to an increased risk of oral diseases and possible changes in oral microecology. In this study, we aimed to assess changes in the microbial community of supragingival plaques to explore the effects of spaceflight microgravity environment on oral microecology. Sixteen healthy male volunteers were recruited, and supragingival plaque samples were collected under -6°head-down bed rest (HDBR) at five-time points: day 1 before HDBR; days 5, 10, and 15 of HDBR; and day 6 of recovery. Bacterial genomic DNA was sequenced using gene sequencing technology with 16S ribosomal ribonucleic acid V3-V4 hypervariable region amplification and the obtained data were analyzed bioinformatically. Alpha diversity analysis showed a significant increase in species richness in supragingival plaque samples on day 15 of HDBR compared with that at pre-HDBR. Beta diversity analysis revealed that the community composition differed among the groups. Species distribution showed that, compared with those at pre-HDBR, the relative abundances of Corynebacterium and Aggregatibacter increased significantly during HDBR, while those of Veillonella, Streptococcus, and Lautropia decreased significantly. Moreover, compared with those at pre-HDBR, the relative abundance of Leptotrichia increased significantly on day 6 of recovery, whereas the relative abundances of Porphyromonas and Streptococcus decreased significantly. Network analysis showed that the interaction relationship between the dominant genera became simpler during HDBR, and the positive and negative correlations between them showed dynamic changes. Phylogenetic investigation of communities by reconstruction of unobserved states analysis showed that the amino acid metabolism function of plaque microorganisms was more enriched during HDBR. In summary, in a 15-day simulated microgravity environment, the diversity, species distribution, interaction relationship, and metabolic function of the supragingival plaque microbial community changed, which suggests that microgravity may affect the oral microecosystem by changing the balance of supragingival plaque microbial communities and further leading to the occurrence and development of oral diseases.